Comparing Hypofractionated With Conventional Fractionated Radiotherapy After Breast-Conserving Surgery for Early Breast Cancer: A Meta-Analysis of Randomized Controlled Trials - Gu, Lihu; Dai, Wei; Fu, Rongrong; Lu, Hongfeng; Shen, Jingyi; Shi, Yetan; Zhang, Mengting; Jiang, Ke; Wu, Feng (Frontiers in Oncology, 2021)
Background The purpose of this meta-analysis was to compare the safety and efficacy between hypofractionated and conventional fractionation radiotherapy in patients with early-stage breast cancer after breast-conserving surgery. Methods We conducted a comprehensive search of PubMed, Embase, Web of Science, and the Cochrane Library to identify relevant randomized controlled trials (RCTs) published before February 2021. At the same time, the hazard ratio (HR), risk ratio (RR), and 95% confidence interval (CI) were calculated to evaluate local recurrence (LR), relapse-free survival (RFS), overall survival (OS), adverse events, and cosmetic outcomes. Results A total of 14 articles were included in this meta-analysis. Four thousand eight hundred and sixty-nine patients were randomly assigned to the control group to receive conventional radiotherapy (CFRT); 6,072 patients were randomly assigned to the experimental group and treated with hypofractionated radiotherapy (HFRT). The results showed that there was no statistical difference between HFRT and CFRT in LR (HR = 0.99, 95%CI = 0.97–1.02, p = 0.476), RFS (HR = 0.99, 95%CI = 0.97–1.02, p = 0.485), OS (HR = 1.00, 95%CI = 0.97–1.03, p = 0.879), and cosmetic outcomes (RR = 1.03, 95%CI = 0.95–1.12, p = 0.53). In addition, HFRT showed fewer severe adverse reactions such as acute skin toxicity, induration, breast atrophy, and pain. Conclusion Our results suggest that there is no statistical difference between HFRT and CFRT in terms of LR, RFS, OS, and cosmetic outcomes. HFRT reduces the risk of developing toxicity reactions compared to CFRT. HFRT may be a better option for patients with early breast cancer after breast-conserving surgery.